The future of food: biotechnology markets and policies in an international setting - Pardey, Philip G. (International Food Policy Research Institute, 2001)
What is the future of food? Everyone agrees that feeding the world in the decades ahead will require substantial increases in crop yields. But how we get there has become a remarkably contentious question because of biotechnology. What should be biotechnology’s role in assuring affordable and sustainably grown food for all? How we answer this question now will have profound ramifications for decades to come. The chapters in this book confront the controversy over biotechnology with new analyses and insights from economists and technologists. The topics covered include the differences in perceptions about biotechnology among rich and poor countries; the effects of rich-country restrictions on international trade in genetically modified crops on the welfare of poorer countries; the effects of intellectual property rights on the bioscience done by public agencies the world over; and the economic impacts of biotechnology.